Arginase-1 and Treg Profile Appear to Modulate Inflammatory Process in Patients with Chronic Gastritis: IL-33 May Be the Alarm Cytokine in H. pylori-Positive Patients. (20th June 2019) - da Silva, Emerson Abdulmassih Wood; da Silva, Natalia Maria Jacom Wood; Rodrigues, Rafael Rocha; Adad, Sheila Jorge; de Lima Pereira, Sanívia Aparecida; Ribeiro, Betânia Maria; Mendonça, Mônica Sawan; Helmo, Fernanda R.; Rodrigues, Virmondes; Rodrigues, Denise Bertulucci Rocha
Abstract : Helicobacter pylori ( H. pylori ) is a highly prevalent bacterium in our environment, directly involved in various upper digestive tract diseases, such as gastritis, peptic ulcer, and gastric cancer. Several molecules activating the immune system have been reported to be involved in containing H. pylori infection. This study is aimed at analyzing the mRNA expression of the cytokines IFN-γ, IL-17, IL-10, TGF-β, IL-6, IL-22, IL-23, and IL-33 ; transcription factors T-bet, RORC, and FOXP3 ; enzymes ARG1, ARG2, and NOS2 ; and neuropeptides VIP and TAC and their respective receptors VIPR1 and TACR1 in the stomach lining of patients with severe digestive disorders. One hundred and twenty six patients have been evaluated, presenting with symptoms in the upper digestive tract, with the clinical indication for an Upper Digestive Endoscopy exam. Two fragments of the mucosa of the gastric body and antrum have been collected for anatomopathological examination and to analyze the expression of enzymes, cytokines, and transcription factors using qPCR. Expression of the ARG1 gene was seen as significantly higher in the group of patients with chronic inactive gastritis than in the control group. Expression of the TGF-β gene and its FOXP3 transcription factor was significantly higher in the group of chronic inactive gastritis patients than in the control. Expression of IFN-γ, IL-17, IL-10, and TGF-β and the transcription factors, T-bet and RORC, in the presence or absence of H. pylori showed no significant difference. However, the expression of FOXP3 was significantly lower in H. pylori -positive patients than that in H. pylori -negative patients. ARG1 and Treg profile appeared to be modulating the inflammatory process, protecting patients from the tissue lesions with chronic inactive gastritis. Furthermore, we suggest that IL-33 may be a crucial mediator of the immune response against an infection, after gastric mucosal damage.